2020
DOI: 10.1111/icad.12416
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal patterns in tachinid parasitoid diversity (Diptera: Tachinidae): a review of the evidence

Abstract: Insect parasitoids may be an exception to the typical biogeographic pattern of increasing species richness at lower latitudes exhibited by most taxa. Evidence for this ‘anomalous’ latitudinal gradient has been derived from observations of hymenopteran parasitoids and it has been argued that other parasitoid groups should show a similar pattern of diversity. Several mechanisms have been proposed to explain this disparity, most notably the nasty host and resource fragmentation hypotheses. We review and evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
1
5
1
Order By: Relevance
“…The results of this study revealed that a small proportion of actual species was found (15% or 199 species) of estimated (1275 species), suggesting that many of the 85% of longhorn beetle species in Thailand were not collected with support from the non-asymptotic species accumulation curve, based on Taxa S, as depicted in Figure 2 a. This tendency was similar in previous studies that reported 20–50% of the estimated number of longhorn species not being recorded [ 13 , 35 , 36 ], and other insect studies showed various percentages of undiscovered species; for example, 24–44% of ant species in the western Amazonian rainforest of Ecuador [ 37 ]; 10–20% of Auchenorrhyncha and Diptera in the tropical forests of Thailand [ 38 ]; and 18% of the Empidoidea community in Doi Inthanon National Park, Thailand [ 39 ]. Therefore, additional intensive survey with several combined sampling methods are necessary in order to evaluate Cerambycidae fauna in Thailand.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study revealed that a small proportion of actual species was found (15% or 199 species) of estimated (1275 species), suggesting that many of the 85% of longhorn beetle species in Thailand were not collected with support from the non-asymptotic species accumulation curve, based on Taxa S, as depicted in Figure 2 a. This tendency was similar in previous studies that reported 20–50% of the estimated number of longhorn species not being recorded [ 13 , 35 , 36 ], and other insect studies showed various percentages of undiscovered species; for example, 24–44% of ant species in the western Amazonian rainforest of Ecuador [ 37 ]; 10–20% of Auchenorrhyncha and Diptera in the tropical forests of Thailand [ 38 ]; and 18% of the Empidoidea community in Doi Inthanon National Park, Thailand [ 39 ]. Therefore, additional intensive survey with several combined sampling methods are necessary in order to evaluate Cerambycidae fauna in Thailand.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study indicated that the relationship between species richness and elevation was significantly negative with hump-shaped patterns and the number of species increasing by elevation at the initial phase; then peaking at the middle-elevation before decreasing at the high elevation. These characteristics are accepted as a general pattern [ 49 ] that is found in several examples of insect distribution, including that of plant species richness, which decreases with increasing elevation [ 36 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Middle elevations have many factors which make them suitable for insects such as optimal temperatures, greater host plant diversity or food availability.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated the high sampling efficiency of Malaise traps. We recorded a relatively higher number of species in comparison to previous studies conducted in locations of similar latitudes over similar sampling periods 32 , 34 , 67 , 68 (Table 3 ). For example, Stireman 34 documented 79 species, and estimated a total of 122 species.…”
Section: Discussioncontrasting
confidence: 43%
“…An increase in diversity with an increase in latitude has been demonstrated for many groups of parasitoid wasps (reviewed by Burington et al, 2020). This direction of the latitudinal diversity gradient is opposite to the pattern observed in a majority of taxa (Willig et al, 2003) and indicates that parasitoids demonstrate very unusual responses to environmental variations.…”
Section: Latitudinal Changes In Parasitismmentioning
confidence: 99%